Growth on Chitin Impacts the Transcriptome and Metabolite Profiles of Antibiotic-Producing Vibrio coralliilyticus S2052 and Photobacterium galatheae S2753 - Sonia Giubergia (American Society for Microbiology, 2017)
ABSTRACT Members of the Vibrionaceae family are often associated with chitin-containing organisms, and they are thought to play a major role in chitin degradation. The purpose of the present study was to determine how chitin affects the transcriptome and metabolome of two bioactive Vibrionaceae strains, Vibrio coralliilyticus and Photobacterium galatheae. We focused on chitin degradation genes and secondary metabolites based on the assumption that these molecules in nature confer an advantage to the producer. Growth on chitin caused upregulation of genes related to chitin metabolism and of genes potentially involved in host colonization and/or infection. The expression of genes involved in secondary metabolism was also significantly affected by growth on chitin, in one case being 34-fold upregulated. This was reflected in the metabolome, where the antibiotics andrimid and holomycin were produced in larger amounts on chitin. Other polyketide synthase/ nonribosomal peptide synthetase (PKS-NRPS) clusters in P. galatheae were also strongly upregulated on chitin. Collectively, this suggests that both V. coralliilyticus and P. galatheae have a specific lifestyle for growth on chitin and that their secondary metabolites likely play a crucial role during chitin colonization. IMPORTANCE The bacterial family Vibrionaceae (vibrios) is considered a major player in the degradation of chitin, the most abundant polymer in the marine environment; however, the majority of studies on the topic have focused on a small number of Vibrio species. In this study, we analyzed the genomes of two vibrios to assess their genetic potential for the degradation of chitin. We then used transcriptomics and metabolomics to demonstrate that chitin strongly affects these vibrios at both the transcriptional and metabolic levels. We observed a strong increase in production of secondary metabolites, suggesting an ecological role for these molecules during chitin colonization in the marine environment.